Multi-wavelength lens construction of a Planck and Herschel-detected star-bursting galaxy - Timmons, Nicholas; Cooray, A.; Riechers, D.A.; Nayyeri, H.; Fu, Hai; Jullo, Eric; Gladders, Michael D.; Baes, Maarten; Bussmann, R.S.; Calanog, Jae; Clements, D.L.; da Cunha, E.; et al. (American Astronomical Society, 2016)
We present a source-plane reconstruction of a Herschel and Planck-detected gravitationally lensed dusty star-forming galaxy (DSFG) at z = 1.68 using Hubble, Submillimeter Array (SMA), and Keck observations. The background submillimeter galaxy (SMG) is strongly lensed by a foreground galaxy cluster at z = 0.997 and appears as an arc with a length of ∼15″ in the optical images. The continuum dust emission, as seen by SMA, is limited to a single knot within this arc. We present a lens model with source-plane reconstructions at several wavelengths to show the difference in magnification between the stars and dust, and highlight the importance of multi-wavelength lens models for studies involving lensed DSFGs. We estimate the physical properties of the galaxy by fitting the flux densities to model spectral energy distributions leading to a magnification-corrected starformation rate (SFR) of 390 ± 60 M yr−1 and a stellar mass of 1.1 ± 0.4 10 x 11 M. These values are consistent with high-redshift massive galaxies that have formed most of their stars already. The estimated gas-to-baryon fraction, molecular gas surface density, and SFR surface density have values of 0.43 ± 0.13, 350 ± 200 M pc−2, and ~ 12 7 M yr−1 kpc−2, respectively. The ratio of SFR surface density to molecular gas surface density puts this among the most star-forming systems, similar to other measured SMGs and local ULIRGs.